Traceability of potential enterotoxigenic Bacillus cereus from bee-pollen samples from Argentina at different sampling throughout the production process - López, Ana Claudia (2019)
Bee-pollen is the result of the agglutination of pollen grains collected from flowers and mixed with nectar and salivary secretions by honeybees. Bee-pollen is a functional food sold for human and animal consumption but also is a favorable microhabitat for many spore-forming bacteria. Among them, Bacillus cereus is a ubiquitous Gram-positive spore-forming bacterium found in soil, plants, and enteric tracts of insects; these niches include honey and pollen. B. cereus can produce several toxins and other virulence factors causing an emetic or diarrheal syndrome after ingestion. This work aimed to study the traceability of potential enterotoxic Bacillus cereus based on colony counts, rep-fingerprinting and toxigenic profiles at four sampling points of the production process